HUBUNGAN KEKUATAN OTOT LENGAN BAHU DAN KOORDINASI MATA-TANGAN TERHADAP HASIL AKURASI SERVIS ATAS PADA TIM BOLA VOLI PUTRA SMA YLPI PEKANBARU - Maestro, Herrian Maestro; Wijayanti, Ni Putu Nita Wijayanti Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : based of observations field researchers found problems at a time when the male team vollyeball YLPI High School Pekanbaru do servicing over when hit the ball and then throw up still not good . Therefore, researchers want to find out the problem. This form of research is research of correlation with population's HIGH SCHOOL volleyball team YLPI Pekanbaru. Sampling technique is the technique of total sampling. The samples in this research is the whole of the population, so the entire sample of 12 people. The instruments used in this research is a test of the strength of the shoulder arm muscles in the form of an expanding test dynamometer tests and eye-hand coordination by catching the ball throwing test kastidan test the accuracy of the service. The data is then processed with stasistic, to test normality test with lilifors on a significant level α=0,05, hypothesis put forward is the relationship of muscle strength arm shoulder and hand-eye coordination of the servicing of the accuracy of the results. On the basis of the data processed, it can be inferred the correlation of data obtained in the kooefisien correlation of rcount = 0,81>rtable  = 0,602 and Ha accepted, relationships between variables X 1 and X 2 of the variable Y, there is a significant relationship. Conclusion the hypothesis was accepted with a confidence level of 95 and significant extent α of 0.05, so there was a significant relationship between muscle strength and coordination of shoulder-arm-hand eye towards servicing the accuracy results the male team of volleyball In YLPI High School PekanbaruPekanbaru. Keywords: shoulder muscle strength, hand-eye coordination, accuracy results for servicing.